Kajian Literatur: Hubungan Tingkat Pengetahuan Kesehatan dan Keselamatan Kerja (K3) dengan Kejadian Kecelakaan Kerja - Delly Safira Hedaputri; Rubayat Indradi; Anung Putri Illahika (Perhimpunan Dokter Kedokteran Komunitas dan Kesehatan Masyarakat Indonesia (PDK3MI), 2021)
Introduction: The trend of work accidents increased and gave various impacts ranging from countable losses or direct costs to uncountable losses or indirect costs, makes it a topic that never stops being discussed. This high incidence of work accidents can be caused by three factors, there are: human, work, and the work environment. The level of Occupational Health and Safety (OHS) knowledge, which is included in the human factor is an important point in building a healthy, safe, not polluted work environment, and free of work accidents in order to increase the productivity and efficiency of workers and able to reduce the incidence of work accidents. Objective: This paper aims to know the correlation between the level of OHS knowledge and work accidents. Method: This paper is a quantitative study of kinds of literature. Bibliography like articles and literature books were obtained through several search engines, there are 2 from Google, 10 from Google Books, 17 from Google Scholar, 4 from PubMed, 6 from NCBI, 4 from Science Direct, and 1 from BMC. Criteria for national journals accredited by Sinta (S3-S5) and international journals accredited by Scopus (Q2) and non-Scopus with the longest the publication year of 2015. Results and Discussion: The result of this assessment shows that level of OHS knowledge associated with the incidence of work accidents in which the higher level of OHS knowledge on workers in a workplace would be the lower incidence of work accidents. Conclusion: There is a relationship between the level of OHS knowledge and work accidents. Further research is needed about matters that affect the level of OHS knowledge and other variables that affect work accidents and the relationships in particular sectors.